(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
Care is an important nursing concept. Nursing education should focus on cultivating students performance of caring behaviors to maintain the patient care that is a hallmark of this profession and guard the health of patients. Nursing teachers must understand the factors related to the performance of caring behaviors in students. This knowledge can serve as a reference for the development and teaching strategy of a nursing program. This qualitative study aimed at understanding the factors affecting the performance of caring behaviors by nursing students. This qualitative study was conducted at a science and technology university inNorthern Taiwan. Convenience sampling was used to collect 40 reflective journals from 20 nursing students at the five-year junior college as the study data. Content analysis was used to analyze the data. This study found two themes related to caring behaviors in nursing students: perception of nursing students and inter-subjectivity with patients. The beliefs and perceptions of students are closely linked to their performance of caring behaviors. Greater awareness in nursing students will improve their performance of caring behaviors (e.g., the concept of nursing care, ability to care, empowerment, learning by imitation and inter-subjectivity with patients). Results of this study could serve as a reference for program design and clinical practicum instruction for nursing education, to improve caring behaviors in students.